Fee Speech: Signaling, Risk-Sharing, and the Impact of Fee Structures on Investor Welfare - Das, Sanjiv Ranjan; Sundaram, Rangarajan K. (Review of Financial Studies, 2002)
The fee structure used to compensate investment advisers is central to the study of fund design, and affects investor welfare in at least three ways: (i) by influencing the portfolio-selection incentives of the adviser, (ii) by affecting risk-sharing between adviser and investor, and (iii) through its use as a signal of quality by superior investment advisers. In this paper, we describe a model in which all of these features are present, and use it to compare two popular and contrasting forms of fee contracts, the “fulcrum” and the “incentive” types, from the standpoint of investor welfare. While the former has some undeniably attractive features (that have, in particular, been used by regulators to justify its mandatory use in a mutual fund context), we find surprisingly that it is the latter that is often more attractive from the standpoint of investor welfare. Our model is a flexible one; our conclusions are shown to be robust to many extensions of interest. The results are also extended to consider unrestricted fee structures and competitive markets for fund managers.